2021
DOI: 10.1097/adt.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use and Cognitive Impairment Among Male Adolescents: A Case-control Study

Abstract: Cannabis use by adolescents is a public health problem because it can cause cognitive impairment and educational deterioration. The objective of this study was to assess the prevalence and correlates of cognitive impairment among male adolescents with cannabis use in comparison with a control group. This is a case-control study that included 1682 adolescents who just finished their secondary school. A drug screen was made for all participants. Cognitive assessment using Montreal Cognitive Assessment (MoCA) sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The majority of the past studies have suggested a significant cognitive decline in cannabis abusers compared to non-abusers and healthy controls [13][14][15][16]. Bassiony et al in their case-control study on 1682 adolescents found that adolescents who use cannabis frequently had impairment in cognitive functions, and their total MoCA score was less than the controls [17]. Bartholomew et al reported prospective memory impairments associated with cannabis use in young adults [18].…”
Section: Relationship Between Cannabis Use and Cognitive Functioningmentioning
confidence: 99%
“…The majority of the past studies have suggested a significant cognitive decline in cannabis abusers compared to non-abusers and healthy controls [13][14][15][16]. Bassiony et al in their case-control study on 1682 adolescents found that adolescents who use cannabis frequently had impairment in cognitive functions, and their total MoCA score was less than the controls [17]. Bartholomew et al reported prospective memory impairments associated with cannabis use in young adults [18].…”
Section: Relationship Between Cannabis Use and Cognitive Functioningmentioning
confidence: 99%
“…While originally designed for diagnosis of mild and severe cognitive impairments in the aged population by Nasreddine and colleagues, 20 MoCA and its vernacular versions have been efficiently extended to young adult and adolescent student populations in several studies. [21][22][23][24] Use of MoCA has also been undertaken specifically in Indian students. 25 Using these questionnaire-based instruments, in this study, we investigated the emotional status and cognitive functioning in university students for the exploration of any potential associations.…”
Section: Introductionmentioning
confidence: 99%